Design of Physical Teaching Materials Based on Cognitive Conflict Learning in Direct Current Electricity Integrating Virtual Laboratory - Irfan Luthfi; Fatni Mufit; Mutia Rosiana Nita Putri (Universitas Negeri Padang, 2021)
Learning Physics in the 2013 Curriculum requires students to understand concepts. However, the facts found in the field show that students' understanding of concepts is still low and there are misconceptions, especially on unidirectional electricity. One solution to overcome this problem is to make physics teaching materials based on cognitive conflicts integrating virtual laboratories on unidirectional electrical materials to improve students' conceptual understanding. The aim pf this study was to produce a valid cognitive conflict teaching material design. This type of research was Design / Development Research. Using the Plomp model development which has two stages, namely Preliminary Research, at this stage an initial problem analysis was carried out by conducting concept tests on students using coding techniques and conducting interviews with teachers. The second stage of the Prototype Phase was the development stage by designing the required teaching materials. For the design of teaching materials that have been made, a self-evaluation test was carried out using the Likert formula, after which the expert validation or expert review was carried out using the V Aiken's formula for each indicator. Based on the analysis of the data obtained, it can be explained, at the Preliminary Research stage, it was found that in the same direction electricity material more than 30% of students experienced misconceptions and 50% of students did not understand. Meanwhile, teachers still use conventional learning (lecture method) and insufficient laboratory tools to do practicum. The second stage of the Prototype Phase produces teaching material design based on cognitive conflict. The results of the self-evaluation test showed that teaching materials at the validation level were very valid with an average value of 86.7 and the expert validation test for materials at the validation level was very valid with an average value of 0.87. The conclusion from the acquisition of the assessment of physics teaching material design based on cognitive conflict is declared valid and the characteristics of the teaching material are in accordance with the 2008 Ministry of National Education